ARRHYTHMIA MANAGEMENT IN CARDIOVASCULAR INTENSIVE CARE UNIT (CVICU): A LITERATURE REVIEW - LAKSONO, SIDHI; PUTRA, RAMI PRATAMA (Al-Iqra Medical Journal : Jurnal Berkala Ilmiah Kedokteran, 2024)
Arrhythmia is a disease that can be life-threatening. There are two categories of arrhythmias, namely tachyarrhythmias and bradyarrhythmias. Both can be found in the emergency department (ER), general ward, intensive care unit (ICU), or cardiovascular intensive care unit (CVICU). The prevalence of arrhythmia is around 1.5% - 5% in the world population and what is often found is atrial fibrillation. Arrhythmia cases can be a challenge for doctors or health workers, especially in critical condition patients, so they require a comprehensive management approach in therapy for the causes and comorbidities that the patient has. In this literature review, existing arrhythmia management approaches in CVICUs will be described